Trafficking and Activation of Henipavirus, Parahenipavirus, and Henipa-like Virus Fusion Proteins - Chanakha K. Navaratnarajah; Roberto Cattaneo (Viruses)
Henipaviruses are emerging zoonotic viruses that have caused deadly outbreaks in humans and livestock across several regions of the world. The fusion (F) protein of henipaviruses plays a critical role in viral entry into host cells and represents a key determinant of viral pathogenicity. This review provides a comprehensive analysis of current knowledge regarding trafficking, activation, as well as the role in particle assembly, of henipavirus F proteins. We discuss the unique characteristics of henipavirus F proteins compared to other paramyxovirus fusion proteins, with particular emphasis on their distinctive trafficking and activation mechanisms. Attention is also given to novel henipaviruses that have been detected in hosts other than bats, namely rodents and shrews. These viruses are sufficiently different that the International Committee on Taxonomy of Viruses has proposed a new genus for them, the Parahenipaviruses. We discuss how variations in F protein characteristics between Henipaviruses, Parahenipaviruses, and yet-unclassified henipa-like viruses might influence their trafficking and activation. Understanding these molecular mechanisms is crucial for developing effective therapeutic strategies against henipavirus infections and for predicting the emergence of novel henipavirus strains with pandemic potential.